Persepsi Keuangan dan Kehidupan Sosial Setelah Pensiun - Mitsalina Tantri; Agung Dharmawan Buchdadi; Andry Priharta; Siti Hamidah Rustiana; Eva Herianti (Jurnal Bisnis, Manajemen, dan Keuangan, 2022)
The purpose of this study is to understand the social and financial impact on life after retirement issues from the academic staff of Universitas Muhammadiyah Jakarta. A detailed questionnaire was developed and used to collect primary data from a sample of 95 academic staff at the University of Muhammadiyah Jakarta using a convenient sampling method. Descriptive analysis was used to study the demo charts, their preferences, and preferences on the choice of investment path, retirement goals, and academic staff investment goals. The social components and financial problems of life after retirement were also identified through factor analysis. The main components that explain 46.2% of the variance in the financial problems of life after retirement are: clarity of purpose, optimism, provision, anticipation and preparation, investment confidence, future position, and immediacy. Meanwhile, the main components that explain 50.6% of the variation in academic staff retirement social problems are: retirement roles, depression, financial worries, adjustments, economic trends, predictions, expectations, changes in life responsibilities, and financial advice. While the main components that explain the 45% variation in academic staff retirement planning are: planning, training, trust. Tujuan dari penelitian ini adalah untuk memahami dampak sosial dan keuangan dari isu-isu pada kehidupan setelah pensiun dari tenaga akademik Universitas Muhammadiyah Jakarta. Kuesioner rinci dikembangkan dan digunakan untuk mengumpulkan data primer dari sampel 95 tenaga akademik di Universitas Muhammadiyah Jakarta menggunakan metode pengambilan sampel yang nyaman (convenience sampling). Analisis deskriptif digunakan untuk mempelajari grafik demo, kesukaan dan preferensi mereka pada pemilihan jalan investasi, tujuan pensiun, dan tujuan investasi tenaga akademik. Komponen sosial dan masalah keuangan kehidupan setelah pensiun juga diidentifikasi melalui analisis faktor. Komponen utama yang menjelaskan 46,2% varians dalam masalah keuangan kehidupan setelah pensiun adalah: kejelasan tujuan, optimisme, ketentuan, antisipasi dan persiapan, keyakinan investasi, posisi masa depan, dan kedekatan. Sedangkan komponen utama yang menjelaskan 50,6% variasi masalah sosial pensiun tenaga akademik adalah: peran pensiun, depresi, kekhawatiran keuangan, penyesuaian, ekonomi tren, prediksi, harapan, perubahan dalam tanggung jawab hidup, dan nasihat keuangan. Sedangkan komponen utama yang menjelaskan variasi 45% dalam perencanaan pensiun tenaga akademik adalah: perencanaan, pelatihan, kepercayaan.